2020
DOI: 10.1007/s40626-020-00175-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and physiological adjustments of maize leaves in response to aluminum stress

Abstract: Acidic soils with elevated aluminum (Al) saturations are worldwide distributed and harm the crop production in most of the tropical and subtropical regions. Under these conditions, root elongation may be impaired and thus disturbs water and nutrient uptake. Consequently, physiological responses of plants challenged with excess Al may resemble those of drought stresses. Here, we hypothesized that drought tolerant plants are also Al tolerant due to changes in growth, metabolic and physiological adjustments in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Exposing the plants to 4 mM Al without PA increased the total TCA cycle metabolites by approximately 0.11-fold due to high levels of citric acid, aconitic acid, α-ketoglutaric acid and malic acid ( Figure 3 B). It has been established that primary metabolic constituents associated with Al tolerance are strongly linked to mitochondrial metabolism and OA production [ 2 , 4 , 8 ]. Organic acid production in response to Al stress is the most-characterized mechanism for Al tolerance, with citrate and malate being the common TCA cycle metabolites identified in several plants [ 4 , 8 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Exposing the plants to 4 mM Al without PA increased the total TCA cycle metabolites by approximately 0.11-fold due to high levels of citric acid, aconitic acid, α-ketoglutaric acid and malic acid ( Figure 3 B). It has been established that primary metabolic constituents associated with Al tolerance are strongly linked to mitochondrial metabolism and OA production [ 2 , 4 , 8 ]. Organic acid production in response to Al stress is the most-characterized mechanism for Al tolerance, with citrate and malate being the common TCA cycle metabolites identified in several plants [ 4 , 8 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that primary metabolic constituents associated with Al tolerance are strongly linked to mitochondrial metabolism and OA production [ 2 , 4 , 8 ]. Organic acid production in response to Al stress is the most-characterized mechanism for Al tolerance, with citrate and malate being the common TCA cycle metabolites identified in several plants [ 4 , 8 , 13 ]. For instance, tomatoes produce and secrets malate, which chelate Al ions into non-toxic forms [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that acid-Al stress significantly restrained elongation and dry mass accumulation of roots and shoots and also reduced RWC, Chl content, Pn, and WUE in leaves of apple ( Malus pumila ) or barley ( Hordeum vulgare ) seedlings [ 31 , 32 ]. As compared to Al-sensitive maize variety BRS1010, Al-tolerant BRS1055 accumulated less Al in shoots, accompanied by a significantly higher RGR of shoots under acid-Al stress [ 33 ]. Similar findings were obtained in the current study, which showed that acid-Al-induced growth retardant, Al enrichment, and declines in Chl content, Pn, and photochemical efficiency could be significantly mitigated by the GABA priming in creeping bentgrass plants.…”
Section: Discussionmentioning
confidence: 99%